1988
DOI: 10.1017/s0950268800029253
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidiuminfections in humans with gastroenteritis in Zaria, Nigeria

Abstract: SUMMARYThe stool samples of 75 patients with gastroenteritis and/or loose and watery faeces at three hospitals and one clinic in Zaria were examined for Cryptosporidium. The stool samples were concentrated by the formol-ether method and stained with safranin-methylene blue. Sixteen (21 %) samples were positive. The rate of detection was higher among females (27%) than males (17%) and among adults (29%) than children (8%). The study confirmed the presence and possible significance of Cryptosporidium, which is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
8
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 11 publications
(11 reference statements)
5
8
3
Order By: Relevance
“…Similar to the reports of Mor and Tzipori (2008), and Ayinmode et al (2012) there was statistically insignificant association between the detection of Cryptosporidium oocysts and the presence of house hold pets in the present study. Contrary to the findings of (DuPont et al, 1995;Keusch et al, 1995)., domesticated animals have been reported as reservoir of Cryptosporidium oocysts and hence source of human infections.The prevalence obtained in the present study is in contrast with the higher prevalence reported from Zaria (Kwaga et al, 1988) and other parts of Nigeria such as Jos (Ikeh et al, 2007) and Imo State (Ikechukwu et al, 2011). The observed disparity particularly with Kwaga et al (1988) and Ikeh et al (2007) studies could be attributed to small number of samples collected in their studies.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Similar to the reports of Mor and Tzipori (2008), and Ayinmode et al (2012) there was statistically insignificant association between the detection of Cryptosporidium oocysts and the presence of house hold pets in the present study. Contrary to the findings of (DuPont et al, 1995;Keusch et al, 1995)., domesticated animals have been reported as reservoir of Cryptosporidium oocysts and hence source of human infections.The prevalence obtained in the present study is in contrast with the higher prevalence reported from Zaria (Kwaga et al, 1988) and other parts of Nigeria such as Jos (Ikeh et al, 2007) and Imo State (Ikechukwu et al, 2011). The observed disparity particularly with Kwaga et al (1988) and Ikeh et al (2007) studies could be attributed to small number of samples collected in their studies.…”
Section: Resultscontrasting
confidence: 99%
“…Contrary to the findings of (DuPont et al, 1995;Keusch et al, 1995)., domesticated animals have been reported as reservoir of Cryptosporidium oocysts and hence source of human infections.The prevalence obtained in the present study is in contrast with the higher prevalence reported from Zaria (Kwaga et al, 1988) and other parts of Nigeria such as Jos (Ikeh et al, 2007) and Imo State (Ikechukwu et al, 2011). The observed disparity particularly with Kwaga et al (1988) and Ikeh et al (2007) studies could be attributed to small number of samples collected in their studies. The observation made from this study showed insignificant association between the detection of Cryptosporidium oocysts and the source of drinking water.…”
Section: Resultscontrasting
confidence: 99%
“…This study also has shown that C. parvum infection was higher among patients within 32-41 months, followed by those between 22-31 months of age. This agrees with the findings of [17]. Although the infection was detected among patients in all age groups, the highest incidence of the infection occurred among children older than two years of age.…”
Section: Discussionsupporting
confidence: 92%
“…For effective disease prevention, an understanding of the environmental factors that predispose animals and man to infectious causes of diarrhea like Cryptosporidium species is required (Rossle and Latif, 2013;Collinet-Adler et al, 2015). Although several studies aimed at detecting and identifying Cryptosporidium species in ruminants have been conducted in Nigeria (Kwaga et al, 1988;Maikai et al, 2011;Pam et al, 2013;Danladi and Ugbomoiko, 2015), the knowledge of parasite occurrence and worldwide distribution in animals is still not complete (Xiao, 2010).…”
Section: Introductionmentioning
confidence: 99%